Development and Validation of an EFL Teachers’ Quality Assurance Questionnaire - Giti Sabadoust; Kobra Tavassoli; Gholamhassan Famil Khalil (Journal of Modern Research in English Language Studies)
There is a consensus among researchers and educators that teachers need to be well prepared to improve the quality of education and students’ learning. Nevertheless, little attempt has been made to implement the trends in teachers’ quality assurance (TQA) in the field of language education. To overcome this gap, the researchers developed a questionnaire on English as a Foreign Language (EFL) teachers’ quality assurance to underscore the role of TQA as a valuable part of teachers’ professional knowledge. First, the researchers developed 51 items based on a thorough review of the literature on TQA and interviewing 10 TEFL university professors. Next, the 51-item questionnaire was reviewed and revised based on the university professors’ comments. Then, 52 EFL teachers, who were selected based on convenient sampling, answered the questionnaire in the piloting phase. Subsequently, after refining the items, 207 EFL teachers chosen through convenient sampling responded to the revised questionnaire. Cronbach’s alpha and exploratory factor analysis were applied to evaluate the reliability and construct validity of the questionnaire, respectively. The results showed that the items loaded on four components, which were named as “skills and knowledge, students’ learning and classroom management, working collaboratively, and students’ needs and feelings”. The good results of the reliability and construct validity of the questionnaire imply its potential use to evaluate TQA consistently. Moreover, the EFL teachers’ high agreement with the questionnaire items showed their awareness of the importance of TQA. The findings of this study can offer insights to second language teachers and teacher educators.